Revolutionary Art – Nationalism – Anti-Semitism: The Case of Wagner - Goran Gretić (Anali Hrvatskog Politološkog Društva, 2014)
The article deals with the political aspects of revolutionary art of Richard Wagner. Through reading of Wagner’s artistic-philosophical project by his most influential interpreters – Friedrich Nietzsche, Thomas Mann and Theodor Adorno – author offers intellectual history of the reception of this project. Discourse on Wagner’s revolutionary art leads to the assessment of the influence Wagner’s cultural anti-Semitism and nationalism had on European politics in 20th century.